Advances in the Treatment of Renal Cell Carcinoma - Reynolds, Paul; Stewart, Grant D (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This Special Issue of Cancers focuses on new advances in the treatment of renal cell carcinoma, both surgical and pharmacological (and combinations of these), and novel approaches to tackle treatment resistance and improve our understanding of this phenomenon.